Child-Led Decision Making Process to Assorting Children Voice in Bandung District - Emeralda Aisha (Journal of Childhood Development, 2023)
The research will discuss child participation in the decision-making process, the leadership led by children is essential to be discussed because children often seen as a human who have not capacity to make decisions or always influenced by an adult. Through this research we will seen how children take the decisions using participation in decision-making (PDM) which are upward and downward information flow. The novelty of this research is how children are given the authority to take the decisions. This research are using qualitative research by having FGD with the child members in children's forum and secondary data from literature reviews. As a result of this research,  children using upward information flow to compile children's voices and downward information flow as a part of the cognitive model in decision-making process. The participation of children will not be meaningful if an adult that accompany the children was not trained and professional adult as it was mentioned in this research on how adult able to hinder children voice because of her lack of capacity. In implementing meaningful participation in the decision-making process, it is important for children to have the right access of the right information.